Symbolic Meaning of Batak Simalungun Wedding Ceremony in Sindar Raya Village (A Semiotic Study) - Junifer Siregar; Nanda Saputra; Eva Pratiwi Pane (Britain International for Academic Research (BIAR-Publisher), 2021)
This research describes the meaning of symbols, symbols, or signs contained in the Batak Simalungun wedding ceremony as a semiotic study. Symbols, symbols, or signs can be identified the meaning, use and benefits in the implementation of marriage customs for the Batak Simalungun community which need to be preserved as one of the local wisdom. The meaning of symbols, symbols, or signs is part of the semiotic approach which is the binding factor in his studies. The sign aims to simplify thoughts or ideas to facilitate communication which contains meaning, values, norms, or certain intentions that must be obeyed by the Simalungun Batak community, especially in the Sindarraya area. The signs found in the Simalungun Batak wedding ceremony are mangalo-alo boru na bayu, boras tenger, tondong welcome (mangalo-alo tondong), tombuan na marappang-appang, ambanganni tondong na baru, groceries, jambar, partadingan manurdukhon, tobus huning, panruttuki, uluni omas / tintin marakkup, suhuni appang, padaskon hiou holong, hiou parsimatuaon and panukkunan dishes.